Investigating the Views and Use of Stackable Microcredentials within a Postgraduate Certificate in Academic Practice - Julia Sargent; Bart Rienties; Leigh-Anne Perryman; Elizabeth FitzGerald (Journal of Interactive Media in Education, 2023)
There is increasing interest around the use of microcredentials for upskilling, employability, professional development, and reaching a wide range of learners. However, little discussion exists around the use of microcredentials to contribute towards broader qualifications and accreditation. This paper investigates the use of a series of microcredentials contributing towards a broader Postgraduate Certificate in Academic Practice (PGCAP) qualification. Using a descriptive case study approach, we explore the initial development of this qualification. We also discuss PGCAP learners’ experiences of microcredentials study, drawing on the results of a survey. In doing so, we present both the merits of microcredentials from the learners’ perspectives but also some of the pedagogical and practical considerations involved.